Effect of subcutaneous meloxicam on indicators of acute pain and distress after castration and branding in 2-mo-old beef calves, - Meléndez, Daniela M (J Anim Sci, 2018)
The aim of this study was to assess knife castration and knife castration + branding in 2-mo-old calves, and the effect of a single dose of s.c. meloxicam at mitigating pain indicators. Seventy-one Angus crossbred bull calves (128 ± 18.5 kg of BW) were used in a 3 × 2 factorial design where main factors included procedure: sham (control calves, CT; n = 23), knife (KN; n = 24) or knife + branding (BK; n = 24), and medication: single s.c. administration of lactated ringer solution (NM; n = 35) or a single dose of 0.5 mg/kg of s.c. meloxicam (M; n = 36). Physiological samples were collected at T0, 60, 90, 120, and 180 min and on days 1, 2, 3, and 7 after procedure, whereas behavioral observations were evaluated at 2 to 4 h and 1, 2, 3, and 7 days after procedure. A procedure × time effect (P < 0.01) was observed for cortisol, where KN and BK calves had greater (P ≤ 0.01) cortisol concentrations than CT calves 60 min after the procedure, whereas BK calves had the greatest (P < 0.05) cortisol concentrations, followed by KN calves and by CT calves 90, 120, and 180 min after the procedure. A procedure × time effect (P = 0.01) was observed for tail flicks, where KN and BK calves had a greater (P < 0.05) number of tail flicks than CT calves on days 1 and 3, whereas BK calves had the greatest number of tail flicks, followed by KN calves, and then by CT calves on day 2. Haptoglobin had a procedure × medication × time interaction (P = 0.05), where BK-NM calves had greater haptoglobin concentrations than BK-M, KN-M, and CT calves on days 1 and 3, whereas BK-NM and KN-NM calves had greater haptoglobin concentrations than BK-M, KN-M, and CT calves on day 2 after the procedure. Lying duration and tail flicks had a medication effect (P = 0.04; P < 0.01) where M calves had greater (P < 0.05) lying duration and lower (P < 0.05) number of tail flicks than NM calves 2 to 4 h after procedure. No medication effects (P > 0.10) were observed for salivary cortisol, substance P, and scrotal temperature minutes after the procedure or for cortisol, substance P, serum amyloid-A, stride length, or behavioral observations days after the procedure. Overall, BK calves presented greater physiological and behavioral indicators of acute pain than KN calves, suggesting that the combination of knife castration + branding was more painful. Meloxicam administered s.c. was effective at reducing physiological and behavioral indicators of acute pain associated with knife castration and knife castration + branding.